Sickness certificates in Sweden: did the new guidelines improve their quality? - Nilsing Emma; Söderberg Elsy; Öberg Birgitta (BMC, 2012)
Abstract Background Long-term sickness absence is high in many Western countries. In Sweden and many other countries, decisions on entitlement to sickness benefits and return to work measures are based on information provided by physicians in sickness certificates. The quality demands, as stressed by the Swedish sick leave guidelines from 2008, included accurate sickness certificates with assessment of functioning clearly documented. This study aims to compare quality of sickness certificates between 2007 and 2009 in Östergötland County, Sweden. Quality is defined in terms of descriptions of functioning with the use of activity and participation according to WHO's International Classification of Functioning, Disability and Health (ICF), and in prescriptions of early rehabilitation. Methods During two weeks in 2007 and four weeks in 2009, all certificates had been collected upon arrival to the social insurance office in Östergötland County, Sweden. Four hundred seventy-five new certificates were included in 2007 and 501 in 2009. Prolongations of sick leave were included until the last date of sick listing. Free text on functioning was analysed deductively using the ICF framework, and placed into categories (body functions/structures, activity, participation, no description) for statistical analysis. Results The majority of the certificates were issued for musculoskeletal diseases or mental disorders. Text on functioning could be classified into the components of ICF in 65% and 78% of sickness certificates issued in 2007 and 2009, respectively. Descriptions according to body components such as "sensations of pain" or "emotional functions" were given in 58% of the certificates from 2007 and in 65% from 2009. The activity component, for example "walking" or "handling stress", was more frequent in certificates issued in 2009 compared with 2007 (33% versus 26%). Prescriptions of early rehabilitation increased from 27% in 2007 to 35% in 2009, primarily due to more counseling. Conclusions An improvement of the quality between certificates collected in 2007 and 2009 was demonstrated in Östergötland County, Sweden. The certificates from 2009 provided more information linkable to ICF and incorporated an increased use of activity limitations when describing patients' functioning. Still, activity limitations and prescriptions of early rehabilitation were only present in one-third of the sickness certificates.